Good night, sleep tight - Engel, Natalie; Scotton, Rob.; Eberz, Robert (New York : Harper, 2011)
Splat is excited about camping out until his mother surprises him with the news that Spike and Plank will be there, too.
"Beginning reading, 1"--Cover.
004-008.
AD 300
Keywords: Camping -- Juvenile fiction; Cats -- Juvenile fiction; Readers (Primary)